Optimalisasi Sistem Pembayaran Quick Respone Code Indonesian Standard (QRIS) Dalam Mewujudkan Inklusi Keuangan - Nugrah Leksono Putri Handayani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to determine the optimization of the Quick Response Code Indonesian Standard (QRIS) payment system in realizing financial inclusion. The research method used is qualitative descriptive analysis using the literature method by conducting a literature study. The research results show that using QRIS is getting easier because it is able to reach various merchants with integrated mobile banking applications and digital wallets. Optimizing the QRIS payment system can realize and overcome the challenges of financial inclusion in Indonesia and open wider financial access for Indonesian society as a whole.